Training load volume and goal as key factors of performance control in judo - Volkov, A. V.; Panchenko, I. A.; Babchenko, A. P. (Theory and Practice of Physical Culture, 2017)
Accurate training load control and management tools are highly important for the coaching and instruction specialists striving to step up the staged training process efficiency for success in competitions. The study makes a special emphasis on the training load monitoring and management versus its volume and goal. The key objective of the study was to rate contributions of both components of the training process manageable by the coach to design the pre-season training stage in the most efficient and stress-free format for success in competitions. The proposed model was tested in the judo training process and its benefits were demonstrated.